An electrophoretic study on phospholipase A2 isoenzymes in the venoms of Central American crotaline snakes - Valiente Álvarez, Carmen Isabel (1992)
The number and isoelectric points of phospholipase A2 isoenzymes were studied in the venoms of 12 Central American crotaline snakes of the genera Bothrops, Crotalus, Lachesis and Agkistrodon. The study was carried out by using a methodology based on electrophoretic separation of venoms, transfer to nitrocellulose and detection of activity of the bands by an indirect hemolytic assay in agarose-erythrocyte-egg yolk gels. All venoms tested had indirect hemolytic activity, although they varied in the number and isoelectric point of their phospholipases A2. Most venoms had predominantly acidic isoenzymes, with the exception of A. bilineatus which had mainly basic isoenzymes and B. schlegelii which had both acidic and basic isoenzymes. Analysis of interindividual variability in B. asper venom demonstrated that two phospholipase A2 isoenzymes are present in some venoms but absent in others. Polyvalent antivenom was effective in neutralizing phospholipase A2 activity of the 12 venoms tested, when venoms and antivenom were incubated in the fluid phase. This work demonstrates a conspicuous interspecific variability in the number and isoelectric points of phospholipases A2 present in Central American crotaline snake venoms